Chitosan as a sustainable alternative for fresh food packaging: Structural insights, modification strategies, and innovations for commercial viability - Olunusi, Samuel Olugbenga; Nor Hanuni, Ramli; Fatmawati, Adam; Hossain, Emran; Kim, Tak H. (Elsevier Ltd, 2025)
The unparalleled physicochemical properties and techno-economic gain of single-use plastics have made their replacement in fresh food packaging highly challenging. However, their increasing non-biodegradability and microplastic pollution across ecosystems have highlighted the urgent need for biodegradable, sustainable, and multifunctional biomaterials. Chitosan, derived from partially deacetylated chitin from crustacean waste, has emerged as a promising alternative due to its biodegradability, film-forming ability, biocompatibility, and antimicrobial activity. Despite its low mechanical properties, poor thermal stability, and high water permeability, advancements in chemical modifications, biopolymer blends, and nanocomposite reinforcement have significantly enhanced its functionality. In addition, its abundant availability and cost-effectiveness make it economically and commercially viable. This review provides comprehensive insights into chitosan's molecular structure, including the backbones and their functions. Additionally, it elucidates the physicochemical and biological properties, modification strategies, and the mechanisms underlying its antimicrobial and antioxidant activities. Moreover, the latest advancements in biosafety, cytocompatibility, and emerging applications in fresh food packaging are explicitly examined. By addressing current challenges and opportunities, this review highlights the potential of chitosan as a multifunctional biomaterial for sustainable food preservation, promoting its commercial adoption to replace single-use plastics.